Minimum 10-year outcomes of primary arthroscopic transosseous-equivalent double-row rotator cuff repair - Johannsen, Adam; Arner, Justin W.; Elrick, Bryant P.; Nolte, Philip-Christian; Rakowski, Dylan R.; Horan, Marilee P.; Millett, Peter J. (The American journal of sports medicine, 2021)
BACKGROUND: Modern rotator cuff repair techniques demonstrate favorable early and midterm outcomes, but long-term results have yet to be reported. - PURPOSE: To determine 10-year outcomes and survivorship after arthroscopic double-row transosseous-equivalent (TOE) rotator cuff repair. - STUDY DESIGN: Case series; Level of evidence 4. - METHODS: The primary TOE rotator cuff repair procedure was performed using either a knotted suture bridge or knotless tape bridge technique on a series of patients with 1 to 3 tendon full-thickness rotator cuff tears involving the supraspinatus. Only patients who were 10 years postsurgery were included. Patient-reported outcomes were collected pre- and postoperatively, including American Shoulder and Elbow Surgeons (ASES), 12-Item Short Form Health Survey (SF-12), Single Assessment Numeric Evaluation (SANE), shortened version of the Disabilities of the Arm, Shoulder and Hand (QuickDASH), and satisfaction. Kaplan-Meier survivorship analysis was performed. Failure was defined as progression to revision surgery. - RESULTS: A total of 91 shoulders (56 men, 31 women) were included between October 2005 and December 2009. Mean follow-up was 11.5 years (range, 10.0-14.1 years). Of 91 shoulders, 5 (5.5%) failed and required revision surgery. Patient-reported outcomes for patients who survived were known for 80% (69/86). Outcomes scores at final follow-up were as follows: ASES, 93.1 ± 10.8; SANE, 87.5 ± 14.2; QuickDASH, 11.1 ± 13.5; and SF-12 physical component summary (PCS), 49.2 ± 10.1. There were statistically significant declines in ASES, SANE, and SF-12 PCS from the 5-year to 10-year follow-up, but none of these changes met the minimally clinically important difference threshold. Median satisfaction at final follow-up was 10 (range, 3-10). From this cohort, Kaplan-Meier survivorship demonstrated a 94.4% survival rate at a minimum of 10 years. - CONCLUSION: Arthroscopic TOE rotator cuff repair demonstrates high patient satisfaction and low revision rates at a mean follow-up of 11.5 years. This information may be directly utilized in surgical decision making and preoperative patient counseling regarding the longevity of modern double-row rotator cuff repair.